2020
DOI: 10.1101/2020.10.26.20220160
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Features of C-reactive protein in COVID-19 patients with different ages, clinical types and outcomes: a cohort study

Abstract: Background: To characterize C-reactive protein (CRP) changes features from patients with coronavirus disease 2019 (COVID-19) and to quantify the correlation between CRP value and clinical classification. Methods: This was a bidirectional observational cohort study. All laboratory confirmed COVID-19 patients hospitalized in Xiangyang No.1 People's Hospital were included. Patients' general information, clinical type, CRP value and outcome were collected. Patients were grouped according to the age, clinical type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Antibodies were detected in large concentrations in female’s bloodstream and these antibodies stay longer in females than in males [ 83 ]. Pearson correlation analysis observed a positive correlation between the CRP, D-Dimer and age of COVID-19 diabetic and non-diabetic patients which showed similarities with Qu et al [ 84 ], and Zhao et al [ 85 ]. The author also stated that more serious conditions had a higher value of CRP and D-Dimer, as well as a longer disease-elevating time, a faster rate of increase, and a slower recovery and the inflammatory reaction was more intense as people became older.…”
Section: Discussionsupporting
confidence: 80%
“…Antibodies were detected in large concentrations in female’s bloodstream and these antibodies stay longer in females than in males [ 83 ]. Pearson correlation analysis observed a positive correlation between the CRP, D-Dimer and age of COVID-19 diabetic and non-diabetic patients which showed similarities with Qu et al [ 84 ], and Zhao et al [ 85 ]. The author also stated that more serious conditions had a higher value of CRP and D-Dimer, as well as a longer disease-elevating time, a faster rate of increase, and a slower recovery and the inflammatory reaction was more intense as people became older.…”
Section: Discussionsupporting
confidence: 80%
“…According to research, 16,51 D‐dimer levels of more than 1 mg/L are associated with a bad outcome in COVID‐19 patients. CRP and D‐dimer have both been linked to a shorter recovery and an increased inflammatory response, particularly as people get older 52,53 . The total mortality rate was 35.4% (n = 148), with 42.3% (n = 118) among patients with severe disease, 34.6% (n = 27) among those with intermediate disease, and 4.9% (n = 3) among those with mild disease ( P value 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, a study of 131 patients showed persistently rising values of CRP was associated with higher levels of mortality among COVID-19 patients. 16 D-dimer, formed by the activation of the plasmin enzyme, indicates the presence of broken-down fibrin in the bloodstream and represents the activation of coagulation and fibrinolysis systems. 17 Studies have indicated that higher levels of D-dimer were associated with more severe disease due to various reasons like increased levels of pro-inflammatory cytokines, thrombosis leading to venous thromboembolism and severe sepsis which leads to increased levels of plasminogen activator inhibitor 1, and excessive fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%